Population-based study on hospital admissions for pediatric status asthmaticus: from before to after the COVID-19 pandemic - Siu, Ka Ka; Yu, Michael Kwan Leung; Rosa Duque, Jaime S.; Chan, Sophelia Hoi Shan; Lau, Yu Lung; Lee, So Lun (Frontiers in Pediatrics, 2025)
ObjectivesThe increase in respiratory infections post-COVID-19 pandemic, attributed to relaxed masking and social distancing, has raised concerns about a new pattern of severe asthma exacerbations in children. We compare admission rates, severity, and risk factors of status asthmaticus in children with reference to the past 3 years before, during, and after the COVID-19 pandemic.Study designThis is a population-based cross-sectional analysis. Admission records were retrieved from the Clinical Data Analysis and Reporting System of the Hospital Authority in Hong Kong. Patients aged 2 to <18 years admitted for status asthmaticus between January 2017 and March 2024 were included.Main resultsThe incidence rate of pediatric status asthmaticus increased after the COVID-19 period compared to before COVID-19 (5.7–7.3 per 100,000 children aged 2 to <18 years), with a higher increase in children aged 2 to <6 years (10.1–20.6 per 100,000 children aged 2 to <18 years). There was a higher percentage of status asthmaticus admissions among total pediatric asthma admissions after COVID-19 (0.83% vs. 2.87%, p < 0.0001). Admissions are predicted to return to before COVID-19 levels by 2025.ConclusionsStatus asthmaticus increased after the COVID-19 pandemic, particularly in preschoolers. Public health measures during the pandemic may have prevented the children's immune systems from being educated with infection.